Burns and scalds in pre-school children attending accident and emergency: accident or abuse?. Issue 3 (1st May 2001) - Benger, J R; McCabe, S E
Abstract : Objectives —To assess how frequently and adequately information relating to the possibility of non-accidental injury (NAI) is documented and considered by doctors assessing pre-school children with burns and scalds in the accident and emergency (A&E) department, and to determine the effect of introducing a routine reminder mechanism into the A&E notes, coupled with an improved programme of NAI education and awareness. Methods —The records of 100 pre-school children attending an A&E department with a burn or scald were reviewed against nine pre-determined standards. Changes in policy were instituted, through a programme of education and the use of a reminder checklist, and the next 100 cases re-audited against the same checklist. Results —Groups one and two were similar in their demographic characteristics. The reminder checklist was included in 60% of group two notes, and when included was completed in 97%. The child protection register was rarely consulted. There was a statistically significant increase in recording the following: time that the injury had occurred, the consistency of the history, the compatibility of the injury with the history given, the consideration of the possibility of NAI, the general state and behaviour of the child and the presence or absence of any other injuries. The rate of referral for a further opinion regarding the possibility of NAI increased from 0 to 3%, but failed to reach statistical significance. Conclusions —Prevailing awareness and documentation regarding the possibility of NAI was found to be poor, but a programme of intervention combining education and the use of a reminder checklist improved both awareness and documentation of NAI, as well as referral rates for further assessment. This strategy may prove applicable to children of all ages and injury types, reducing the number of cases of child abuse that are overlooked in the A&E department.